Aggressive interactions between juvenile swordfishes and blue sharks in the Western Mediterranean: a widespread phenomenon? - PENADÉS-SUAY, JAIME; GARCÍA-SALINAS, PABLO; TOMÁS, JESÚS; AZNAR, FRANCISCO JAVIER (Mediterranean Marine Science, 2019)
There are numerous reports of billfishes spearing objects, marine organisms, and even humans. Whether or not this behaviour is intentional and, if so, what is its functional meaning, are open questions. In 2016, an adult blue shark (Prionace glauca) was found to be killed by a juvenile swordfish (Xiphias gladius) in the western Mediterranean. Here we report on three more recent cases involving both species in the same area. In February 2017, an adult male blue shark was found stranded in Garrucha (Spain) with a fragment of a juvenile swordfish’s rostrum (18cm long x 2cm wide at proximal end) inserted in its cranium. In March 2017, an adult pregnant female blue shark was stranded alive on the coast of Ostia (Italy) but died shortly afterwards; a fragment of a juvenile swordfish’s rostrum (25x3cm) was found allocated between the eye and the cranium. Finally, in February 2018, an adult female blue shark appeared stranded in the coast of Vera (Spain), with a putative impalement injury anterior to the right eye but without an associated bill fragment. Surprisingly, X-ray and computed tomography revealed an older injury in the right nostril, with a small piece of a juvenile swordfish’s rostrum (5.3x1.2cm). These cases suggest that juvenile swordfish would drive their rostrum into blue sharks as a defensive strategy that is likely to be far from anecdotal. We suggest that no regular cases of these interactions are reported because they occur at high sea and evidence of them, when available, can easily be overlooked.